2020
DOI: 10.1155/2020/5319640
|View full text |Cite
|
Sign up to set email alerts
|

A Radiographic Study of Biomechanical Relationship between the Achilles Tendon and Plantar Fascia

Abstract: Background. Previously, scholars have concluded that the Achilles tendon and the plantar fascia were closely biomechanically related, although there is little clinical evidence of the relationship between the two. To investigate the biomechanical relationship between the Achilles tendon and the plantar fascia, the author used standing lateral ankle radiographs of patients with insertional Achilles tendonitis to determine the biomechanical relationship between the Achilles tendon and plantar fascia. Methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, these spurs reveal a close morphological relationship with the plantar fascia, which most likely stimulates their growth caused by traction forces. Secondly, this study highlighted the fact www.nature.com/scientificreports/ that spurs form complex three-dimensional structures, which were so far most commonly assessed using twodimensional images both clinically 3,4,7,19,[25][26][27][28][29] and in research 2,10,14,16 . Hence, the enthesis of the plantar fascia in superiorly located spurs can easily be missed, leading to the assumption that the spurs do not develop as a result of external traction forces 9,14 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, these spurs reveal a close morphological relationship with the plantar fascia, which most likely stimulates their growth caused by traction forces. Secondly, this study highlighted the fact www.nature.com/scientificreports/ that spurs form complex three-dimensional structures, which were so far most commonly assessed using twodimensional images both clinically 3,4,7,19,[25][26][27][28][29] and in research 2,10,14,16 . Hence, the enthesis of the plantar fascia in superiorly located spurs can easily be missed, leading to the assumption that the spurs do not develop as a result of external traction forces 9,14 .…”
Section: Discussionmentioning
confidence: 91%
“…This impairs a direct comparison between these observations. Several authors have suggested considering the Achilles tendon, the calcaneus and the plantar fascia as a functional entity, and including the plantar region in the treatment of Achilles tendon pathologies and vice versa [17][18][19][20][21] . The former is supported by the finding that thick collagen fibres are connecting the Achilles tendon and the plantar fascia via the calcaneus in neonates, forming an apophyseal area, which is ossifying throughout life and leaves only the insertions of the soft tissues into the calcaneus 18 .…”
mentioning
confidence: 99%
“…The analysis of the results showed that both the forward tilt of the posture and the observed defects and dysfunctions of the feet can cause the formation of traction forces within the heel apophysis. Lack of heel load and shifting the body weight forward (during standing and walking) causes tension of the plantar flexors of the feet and eccentric tension within the Achilles tendon [ 119 , 120 ]. Thus, through the action of internal forces, i.e., in the course of the plantar structures of the feet to the front of the foot and upwards in the course of the Achilles tendon, this causes pressure on the heel bone, lifting the heel and stretching in opposite directions.…”
Section: Discussionmentioning
confidence: 99%
“…Several radiographic studies reported a relationship between posterior heel spur and plantar heel spur. 30 , 34 Posterior heel spur has been postulated to occur from repetitive traction of the Achilles tendon at the insertion of the calcaneus, resulting in subsequent inflammation and spur formation. Zhu et al in their radiographic study demonstrated the relationship between posterior and plantar heel spurs in patients with insertional Achilles tendonitis.…”
Section: Discussionmentioning
confidence: 99%
“…They explained this relationship by the increasing tension in the biomechanical complex involving the Achilles tendon, calcaneus, and plantar fascia. 34 In contrast, other authors contend that plantar heel spurs are fundamentally different from posterior heel spurs in the Achilles tendon, citing anatomic investigations that report plantar heel spurs have vertically oriented trabecula rather than horizontally oriented trabecula. 15 , 18 They suggest that calcaneal spurs are fibrocartilaginous outgrowths formed in response to calcaneal stress fractures, which is to protect the calcaneus against microcracks.…”
Section: Discussionmentioning
confidence: 99%